The Ridge and the River: Adapting a novel set in World War Two into a screenplay for a contemporary Australian film audience - Beaton, John Roderick (Curtin University, 2016)
This two-part thesis argues that academic studies of adaptation from novel to film disregard the importance to the screenwriter of industrial and commercial pressures. The first part has a brief overview of adaptation studies, and the art of screenwriting which links to a final chapter about adapting a specific novel into a screenplay, some concerns of screenplay structure and a personal review of tasks ahead. The second part is the creative work of a feature length screenplay.